Mineral Deficiencies Electrolyte Disturbances, Genes, Diet and Disease Interface - Mózsik, Gyula; Díaz-Soto, Gonzalo (IntechOpen, 2021)
Metals, inorganic compounds, and their elements act as cofactors for enzymes that play an essential role in various human biological processes. These mineral nutrients come from the soil and enter the human body through the food chain via plants. A regulated diet with all necessary constituents consumed in an appropriate way maintains cell homeostasis and keeps the body under a physiological state essential for cellular demands. This book deals with problems of mineral deficiencies, which can arise due to decreased consumption of certain foods, malabsorption syndrome, bleeding disorders, a diet with insufficient nutritional content, and so on.